O uso dos jogos e das brincadeiras no processo de alfabetização e letramento - Kretikouski, Daiane Cristina Ottaviani (Universidade Federal de São Carlos, 2024)
This work is a bibliographical research, with the objective of analyzing the contribution that the use of games and games provide in the process of literacy and literacy. Playing is well accepted when we think about Education Childish, however, this perspective changes when six-year-old children They move from this stage to the initial years of Elementary School. The children apparently leave the context of a “playing” child for a rigid teaching environment, with focus on literacy and literacy. Therefore, how does this transition appear for they? How are they received in this new teaching and learning context? What are the benefits that games, toys and activities present during this process? Which is impact that the teacher's positioning brings in the face of differences and the transition of these two phases? The questions presented in this Course Completion Work will be clarified with emphasis on authors such as Magda Soares, Maria Iolanda Monteiro and Marlene Carvalho (to support the concepts of literacy and literacy), Douglas Aparecido de Campos, Maria Aparecida Mello and Tizuko Morchida Kishimoto (who point out the importance of games, toys and games), Claude Lessard, Maurice Tardif and Regina Puccinelli Tancredi (which highlights the actions, faced with the difficulties of everyday teaching, as well as the transition from Early Childhood Education to the early years of Elementary School). The collection of research began in 2022 and in order to delimit the research subject, we chose in carrying out a selection through two online databases, such as the Scielo database and the UFSCar Institutional Repository. It is understood that games and activities are strong allies not only in the literacy and literacy process, but they contribute significantly when it is articulated with the content in a systematic way by the teacher.
The use of games and play in the process of literacy and literacy
Keywords: Alfabetização; Brincadeira; Jogo; Letramento; CIENCIAS HUMANAS